Resenha de La traduction en citations: florilège - Leurquin, Eric Claude (2021)
The review presents the book by Jean Delisle La traduction en citations. The book contains more than 2,700 aphorisms, opinions, testimonies on translation, definitions, eulogies, epigrams, that the author has gathered in this book from more than eight hundred authors, from Antiquity to the present day, following different theoretical approaches.